Evaluation of trade performance dynamics in Serbia using ARAT and Rough MABAC methods - Lukić, Radojko (Oeconomica Jadertina, 2024)
Recently, there has been an increasing amount of literature dedicated to the importance and specifics of applying multi-criteria decision-making methods in trade. These methods, given that they are based on a mathematical approach, provide realistic results of the analysis of the treated problem. Based on that, this study investigates the dynamics of trade performance in Serbia based on the ARAT (Interval and Iterative Preference/Priority Scale), and the Rough MABAC (Multi-Attributive Border Approximation Area Comparison) method. The results of the study show that in 2023, the best performance of trade in Serbia was achieved. The worst performance of trade in Serbia was achieved in 2018. The ranking of trade performance in Serbia is as follows: 2023, 2022, 2021, 2020, 2019 and 2018. The performance of trade in Serbia has continuously improved. Effective management of human resources, investments, capital, sales, and profit contributed to this. Certainly, the positive influence of other relevant factors (foreign direct investments, new business models - multichannel sales: store and electronic, private brand, sale of organic products, the concept of sustainable development - economic, social, and environmental dimensions, the idea of social responsibility) must not be neglected. , digitization of the entire business, etc.). To achieve the target profit in Serbian trade, adequate adaptation to dynamic complex changes in the business environment and macroeconomic trends (geopolitical situation, energy crisis, inflation, exchange rate, interest rates, etc.) is important. In all this, digitizing the entire trade business plays a significant role.